Figure-eight arylene ethynylene macrocycles: facile synthesis and specific binding behavior toward Hg2+. Issue 24 (8th October 2021) - Nie, Hui; Li, Qian-Hui; Zhang, Siqi; Wang, Chuan-Ming; Lin, Wen-Hui; Deng, Ke; Shu, Li-Jin; Zeng, Qing-Dao; Wan, Jun-Hua
Abstract : Two figure-eight arylene ethynylene macrocycles (AEMs) were synthesized from non-helical precursors and the figure-eight shape was clearly imaged by STM. Abstract : Figure-eight (lemniscular) shaped macrocycles, besides their esthetic beauty, often have interesting chiroptical properties. However, only limited figure-eight carbocyclic frameworks have been reported as yet and most of them have been acquired by dimerizing helicenes with inherently helical structures. Herein a novel figure-eight carbocyclic framework, lemniscular arylene ethynylene macrocycle (AEM), was firstly synthesized from non-helical precursors. By simply increasing the reactant concentration, intramolecular cyclization was effectively suppressed, while intermolecular cyclization was significantly increased to obtain figure-eight macrocycles in acceptable yields. Scanning tunneling microscopy (STM) investigation was firstly employed to confirm the figure-eight shape through molecular imaging. Furthermore, the figure-eight cyclization mechanism was systematically discussed. Interestingly, macrocycles bearing inner –NH2 groups (SPM-Q6-NH2 and SPM-Q12-NH2 ) showed a specific sensing behavior toward highly toxic Hg 2+ . Even more intriguing is that, compared to planar macrocycle SPM-Q6-NH2, its figure-eight dimer (SPM-Q12-NH2 ) exhibited much stronger complexation with Hg 2+ . This study opens up a new way to construct figure-eight conjugated carbocyclic macrocycles from an inherently non-helical precursor. More importantly, with this figure-eight AEM as a molecular platform, further structural derivations can be achieved through simple cycloaddition reactions with unsaturated bonds (ethynylene bonds and diyne bonds) or introducing donor–acceptor (D–A) structures.